Pendampingan Penggunaan Financial Technology Di Era Society 5.0 Di Desa Saribaye Kecamatan Lingsar Lobar - Nurabiah, Nurabiah; Pusparini, Herlina; Fitriyah, Nur; Bambang, Bambang; Mariadi, Yusli; Aprilian, Imam Yuardi; Setiawati, Rani; Santoso, Aprilia; Wulan, Putri Cahya (Universitas Mataram, 2024)
Saribaye Village is one of the villages in NTB that is of concern for financial literacy issues. One of the programs held by the NTB Province OJK is the